Kyrgyz Republic : Gold is Not Enough - World Bank (World Bank, Washington, DC, 2017)
A new coalition government was formed in September 2012 following the collapse of the previous government at the end of August 2012. The Kyrgyz economy experienced a significant decline during the first half of 2012 caused by disrupted operations at the Kumtor gold mine. A decline in gold exports combined with a higher level of imports has increased the current account deficit. Expansionary fiscal policy during the first half of the year along with revenue weakness during the remainder of the year will widen the fiscal deficit to 6.1 percent of gross domestic product (GDP) in 2012 from 4.8 percent of GDP a year ago. The medium-term growth outlook is favorable although there are significant downside risks. There are also exogenous shocks that will need to be mitigated, including rising food prices, spillover effects from the Euro zone sovereign debt crisis, and a weak global economy.